High-performance NdSrCo2O5+δ–Ce0.8Gd0.2O2-δ composite cathodes for electrolyte-supported microtubular solid oxide fuel cells. (8th September 2021) - Wang, Sea-Fue; Hsu, Yung-Fu; Liao, Yi-Le; Huang, Shih-Ting; Jasinski, Piotr
Abstract: NdSrCo2 O5+δ (NSCO) is a perovskite with an electrical conductivity of 1551.3 S cm −1 at 500 °C and 921.7 S cm −1 at 800 °C and has a metal-like temperature dependence. This perovskite is used as the cathode material for Ce0.8 Gd0.2 O2-δ (GDC)-supported microtubular solid oxide fuel cells (MT-SOFCs). The MT-SOFCs fabricated in this study consist of a bilayer anode, comprising a NiO–GDC composite layer and a NiO layer, and a NSCO–GDC composite cathode. Three cell designs with different outer tube diameters, GDC thicknesses, and NSCO/GDC ratios are designed. The MT-SOFC with an outer tube diameter of 1.86 mm, an electrolyte thickness of 180 μm, and a 5NSCO–5GDC composite cathode presents the best performance. The flexural strength of the aforementioned cell is 177 MPa, which is sufficient to confer mechanical integrity to the cell. Moreover, the ohmic and polarization resistance values of the cell are 0.22 and 0.09 Ω cm 2 at 700 °C, respectively, and 0.15 and 0.03 Ω cm 2 at 800 °C, respectively. These results indicate that the NSCO-GDC composite exhibits high electrochemical activity. The maximum power densities of the cell at 700 and 800 °C are 0.46 and 0.67 W cm −2, respectively, exceeding those of existing electrolyte-supported MT-SOFCs with similar electrolyte thicknesses. Highlights: Electrolyte–supported micro-tubular SOFCs with NdSrCo2 O5+δ cathodes were built. NSCO has a very high electrical conductivity and metal-like temperature dependence. Cells with distinct diameters and different NSCO/GDC ratios of cathode were built. Flexural strength of Cell C was 177 MPa enough to confer mechanical cell integrity. Cell C with 180 μm GDC has MODs of 0.46 W·cm −2 at 700 °C and 0.67 W·cm −2 at 800 °C.